Women and war in the Middle East : transnational perspectives - Al-Ali, Nadje Sadig; Pratt, Nicola Christine (Zed Books, 2009)
Women and War in the Middle East provides a critical examination of the relationship between gender and transnationalism in the context of war, peace-building and post-conflict reconstruction in the Middle East.